Synthesis of 5-acetyl-2-arylamino-4-methylthiazole thiosemicarbazones under microwave irradiation and their in vitro anticancer activity. (1st February 2016) - Shi, Hai-Bo; Hu, Wei-Xiao; Zhang, Wei-Mao; Wu, Yan-Fei
A series of 21 new tri- and tetra-cyclic thiosemicarbazone derivatives were prepared via the condensation of morpholine, piperazine or N-(4-methoxyphenyl)piperazine with seven methyl hydrazine-carbodithioate derivatives of 5-acetyl-2-arylamino-4-methylthiazoles under microwave irradiation. All compounds were tested for their cytotoxic activity in vitro against human gastric, lung and breast cancer cell lines. The results showed that some of the compounds displayed moderate anticancer activity. The most potent compound, a morpholino-substituted analogue, exhibited significant activity against human breast cancer cells.